COL1A1::PDGFB fusion-associated uterine sarcoma and response to Imatinib: A case report - Udita Chapagain; Hannah R. Krigman; Ian S. Hagemann; Mia C. Weiss; Lulu Sun (Elsevier, 2023)
Uterine sarcomas are rare neoplasms of the uterus, some of which are associated with distinctive gene fusions. COL1A1::PDGFB fusion uterine sarcoma is a recently described entity that shares the same genetic alteration as dermatofibrosarcoma protuberans. These uterine sarcomas have a nonspecific spindle cell sarcoma appearance and are CD34 positive by immunohistochemistry. Accurate diagnosis relies on identification of the characteristic fusion by molecular genetic methods. The importance of diagnosing this entity lies in its potential response to targeted therapy with imatinib, a tyrosine kinase inhibitor successfully used in dermatofibrosarcoma protuberans, but only one prior case of COL1A1::PDGFB fusion uterine sarcoma treated with imatinib has been reported. Here, we describe a case of COL1A1::PDGFB fusion uterine sarcoma with response to imatinib after recurrence, with a brief review of this rare tumor.